2020
DOI: 10.21203/rs.3.rs-26132/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-Analysis of Association between CT-based Features and Tumor Spread Through Air Spaces in Lung Adenocarcinoma

Abstract: Objective:Spread through air space (STAS) is a novel invasive pattern of lung adenocarcinoma and is also a risk factor for recurrence and worse prognosis of lung adenocarcinoma after sublobar resection. The aims of this study are to evaluate the association between computed tomography (CT)-based features and STAS for preoperative prediction of STAS in lung adenocarcinoma, eventually, which could help us choose appropriate surgical type. Methods:Systematic research was conducted to search for studies published … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In previous literature, STAS was found to be associated with aggressive clinicopathologic characteristics in surgically resected lung ADC 29 . In imaging finding, STAS is associated with higher pathological stage, a larger tumor diameter, higher presence of solid component, and vascular convergence 30,31 . In terms of pathology finding, STAS was strongly linked to the presence of lymphovascular invasion and high‐grade morphologic patterns, including larger nuclear size, increased mitotic count, and high Ki‐67 labeling index, which suggests that STAS can serve as a marker for tumor proliferation 29,32 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In previous literature, STAS was found to be associated with aggressive clinicopathologic characteristics in surgically resected lung ADC 29 . In imaging finding, STAS is associated with higher pathological stage, a larger tumor diameter, higher presence of solid component, and vascular convergence 30,31 . In terms of pathology finding, STAS was strongly linked to the presence of lymphovascular invasion and high‐grade morphologic patterns, including larger nuclear size, increased mitotic count, and high Ki‐67 labeling index, which suggests that STAS can serve as a marker for tumor proliferation 29,32 .…”
Section: Discussionmentioning
confidence: 82%
“…29 In imaging finding, STAS is associated with higher pathological stage, a larger tumor diameter, higher presence of solid component, and vascular convergence. 30,31 In terms of pathology finding, STAS was strongly linked to the presence of lymphovascular invasion and high-grade morphologic patterns, including larger nuclear size, increased mitotic count, and high Ki-67 labeling index, which suggests that STAS can serve as a marker for tumor proliferation. 29,32 Chen et al carried out a multi-institutional study to investigate whether stage I ADC with STAS can benefit from adjuvant chemotherapy.…”
Section: Other Subgroup Analyses Of Stas In Survival Outcomementioning
confidence: 99%
“…While the previous meta-analysis by Yin et al had included studies that reported on this association, they did not strictly include studies that used CT imaging. 24 There were studies that were based solely on histopathology examination. However, in the current meta-analysis, only those studies that used CT-based radiologic investigation were included.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the current meta-analysis provides the most updated data on the association between STAS and CT-based features in patients with lung adenocarcinoma. While the previous meta-analysis by Yin et al had included studies that reported on this association, they did not strictly include studies that used CT imaging 24. There were studies that were based solely on histopathology examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation